2020
DOI: 10.3389/fmicb.2020.00736
|View full text |Cite
|
Sign up to set email alerts
|

Friend or Enemy: A Dual Role of Autophagy in Plant Virus Infection

Abstract: Autophagy is a primary protective process that involves removing damaged organelles or dysfunctional proteins in eukaryotes. The autophagy pathway not only maintains cellular homeostasis, but also modulates the host's cellular response to pathogen infection. Several studies proved that autophagy plays a dominant role in plant fitness and immunity. As intracellular parasites, the replication and spread of viruses entirely rely upon the molecular machinery of the host cell, including the autophagy process. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…The roles of selective autophagy in plant–pathogen interactions have been extensively reviewed recently [ 10 , 12 , 41 , 46 , 47 ]. Here, we just briefly review the arms race between plant and pathogens and focus our attention on the newest findings.…”
Section: Selective Autophagy—a Battlefield Between Plant–pathogen mentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of selective autophagy in plant–pathogen interactions have been extensively reviewed recently [ 10 , 12 , 41 , 46 , 47 ]. Here, we just briefly review the arms race between plant and pathogens and focus our attention on the newest findings.…”
Section: Selective Autophagy—a Battlefield Between Plant–pathogen mentioning
confidence: 99%
“…Recently, Marshall et al [ 21 ] showed that inactive 26S proteasomes are removed via a mechanism called proteaphagy, establishing a functional link between the two major degradation pathways. Furthermore, selective autophagy also plays a critical role in the clearance of invading pathogens (xenophagy) including bacteria, viruses, and fungi [ 11 , 13 , 39 , 40 , 41 ]. Since numerous excellent reviews have covered the pexophagy [ 42 , 43 ], chloropahgy [ 28 , 44 , 45 ], ER-phagy [ 3 ], proteaphagy [ 21 ], and xenophagy [ 11 , 13 , 41 , 46 , 47 ], we just focus our attention on the newly emerged features and the novel roles of the selective autophagy in response to both biotic and abiotic stresses in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the microarray study, Laura et al found that many genes involved in autophagy pathway were up-regulated in tomato after infection by tomato yellow leaf curl Sardinia virus [8]. Many reports have demonstrated that autophagy can be activated upon virus infection to play important roles in plant resistance to virus infection [9][10][11][12][13][14]. For example, autophagy can regulate plant hypersensitive cell death (PCD) response to restrict tobacco mosaic virus (TMV) infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the selective autophagy plays central roles in removing protein aggregates [9][10][11][12] and damaged organelles [13][14][15][16][17][18][19] under stress conditions. In addition, selective autophagy also plays a crucial role in the clearance of invading pathogens, such as bacteria, viruses, and fungi [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%